Equipment of Earthquake Detection and Warning with Vibration Sensor - Anggraeni, Dyane Putriera; Aminah, Nonoh Siti; Radiyono, Yohanes (Sebelas Maret University, 2016)
The purposes of writing this paper are to determine: (1) the working principle of vibration sensors can detect impending earthquakes, (2) the sensitivity or the sensitivity of the tool when used in detecting the vibration of an earthquake, (3) demonstration tool Earthquake Detection and Warning with vibration sensor has good meets criteria for use students learn. The method of this research is an a demonstration tool in learning. The basic principle of work and warning earthquake detector with a vibration sensor this is when an earthquake occurs or when the dynamo (earthquake simulator) is started, the resulting vibrations cause movement of the pendulum. This pendulum movement is what will trigger the sound of the bell. When the pendulum movement causes the pendulum in contact with the copper wire ring, then the electricity will flow toward the bell. When electricity flows into the bell will arise in the membrane vibration in the bell. A vibrating membrane will produce resonance which then led to a wave. This wave is what produces the sound on the buzzer. Pendulum vibration frequency is closely related to the magnitude of the voltage / potential difference given input on the dynamo that causes the rotor to rotate. Increasing the voltage will increase the rotational speed of the rotor on a large dynamo. The faster the rotor rotation, the vibration of the pendulum will be even greater. This resulted in the pendulum will be faster and more frequent touching circle copper wire which is connected electricity and bell. Thus the buzzer will sound increasingly rapid and dynamic. The results of the experiment are the greater the number of loops and the greater the voltage will cause a greater rotational speed of the rotor is generated, so that the greater the pendulum vibrations and buzzer / alarm to sound more dynamic. Detector and earthquake warning with vibration sensor has a sensitivity to the number of loops starting from 2 pieces with a 3V input voltage and is capable of detecting an earthquake of â¥3,6 SR. Based on the results of the assessment of a demonstration tool detection and warning of earthquakes with vibration sensor was found that the maximum value that is filled by a validator is 39. It can be concluded that the demonstration tool detection and warning of earthquakes with vibration sensor is included in good criteria for the use of students in learning.